Product Awareness of Account Holders under Pradhan Mantri Jan Dhan Yojana (PMJDY) - Bhuyan, Manoranjan; Das, Kumar Bar; Mohanty, Jitendra (Indian Journal of Finance, 2018)
Non availability of access to formal financial system acts as a critical constraint for economic development for poor and underprivileged people whose number is quite significant in this world. For a long - time, economists were looking for plausible explanations for wide spread poverty, inequality, and unsustainable growth in many parts of the world. When financial inclusion programmes started as a policy response for exclusion, the contents of the programme touched upon some basic issues such as access through an account, creation of awareness, and use of various banking products so that the excluded persons acquire the skill sets to manage money wisely and improve their financial well being. The present study was undertaken to ascertain the product awareness of account holders getting inducted to the formal financial system through one of the largest financial inclusion programmes of the world currently in operation in India under the name of Pradhan Mantri Jan Dhan Programme (PMJDY). A survey was conducted during August 2016 - May 2017 by administering a questionnaire on 453 account holders covering 18 out of 30 districts in Odisha, a state located in the eastern region of India. The findings of the study revealed that while gender influenced the awareness of account holders, general awareness levels of account holders about various basic financial products and services was found to be low, calling for suitable interventions for realizing the full benefits of the programme.